Mesenchymal Stem Cells in Oriented PLGA/ACECM Composite Scaffolds Enhance Structure-Specific Regeneration of Hyaline Cartilage in a Rabbit Model - Weimin Guo; Xifu Zheng; Weiguo Zhang; Mingxue Chen; Zhenyong Wang; Chunxiang Hao; Jingxiang Huang; Zhiguo Yuan; Yu Zhang; Mingjie Wang; Jiang Peng; Aiyuan Wang; et al. (Hindawi Limited, 2018)
Articular cartilage lacks a blood supply and nerves. Hence, articular cartilage regeneration remains a major challenge in orthopedics. Decellularized extracellular matrix- (ECM-) based strategies have recently received particular attention. The structure of native cartilage exhibits complex zonal heterogeneity. Specifically, the development of a tissue-engineered scaffold mimicking the aligned structure of native cartilage would be of great utility in terms of cartilage regeneration. Previously, we fabricated oriented PLGA/ACECM (natural, nanofibrous, articular cartilage ECM) composite scaffolds. In vitro, we found that the scaffolds not only guided seeded cells to proliferate in an aligned manner but also exhibited high biomechanical strength. To detect whether oriented cartilage regeneration was possible in vivo, we used mesenchymal stem cell (MSC)/scaffold constructs to repair cartilage defects. The results showed that cartilage defects could be completely regenerated. Histologically, these became filled with hyaline cartilage and subchondral bone. Moreover, the aligned structure of cartilage was regenerated and was similar to that of native tissue. In conclusion, the MSC/scaffold constructs enhanced the structure-specific regeneration of hyaline cartilage in a rabbit model and may be a promising treatment strategy for the repair of human cartilage defects.